Optimasi Parameter Gravitasi Shot Peening Terhadap Kekasaran, Kekerasan dan Struktur Mikro ST 45 dengan Metode Taguchi - Nur Wibowo, Trio; Hartono, Hartono; Sugiantoro, Bambang (Infotekmesin, 2021)
Shot peening is a surface treatment method at low temperature by shooting steel balls that are continuously adjusted for pressure and speed until plastic deformation is produced. The optimal parameter of the shot peening process was tested with the taguchi distribution. The factors and levels used are processing time, shooting distance and air pressure used in the shot peening process. Observations were made by looking at changes in surface roughness, thickness reduction, hardness levels, wear and changes in the microstructure of ST 45 steel material. The greatest hardness of 240.39 HVN was obtained at 10 minutes, a distance of 10 cm and a pressure of 9 kg / cm². The results of the surface wear test with the smallest value of 0.00039 mm³ / kg.m were obtained at 5 minutes, a distance of 10 cm and a pressure of 7 kg / cm². The results of the microstructure test showed that the change in the grain size of the microstructure of the material became flatter and smaller, the gravity shot peening method improved the mechanical properties of the ST 45 material.